Leaders' impact on public spending priorities: The case of the German Laender - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
We examine determinants of the composition of public expenditure in the German Laender (states) over the period 1993-2008, as the Laender exhibit a high degree of institutional and political homogeneity and are endowed with extensive fiscal competences. Our prime contribution is an investigation into how political leaders' socioeconomic background influences public spending priorities. Applying sociological theory, we link preferences for the composition of public spending to social status. In contrast to approaches relying on political budget cycles or partisan theory, we find strong and theory-consistent evidence that prime ministers tend to favour fiscal policies supporting the social class in which they are socialised. Governments led by prime ministers from a poor socioeconomic background spend significantly more on social security, education, health, infrastructure, and public safety.
Keywords: E62; H75; H76; 330; leadership; socioeconomic status; social rivalry; public expenditure composition; Öffentliche Ausgaben; Länderfinanzen; Regierungschef; Sozialer Status; Teilstaat; Schätzung; Deutschland